Minat, Pendapat, dan Aktivitas Remaja terhadap Pembelian Fast Food di Kecamatan Lamongan Kabupaten Lamongan - Chreisty Luzvurry Deisthera; Rahayu Dewi Soeyono; Choirul Anna Nur Afifah; Asrul Bahar (Lembaga Pengembangan Kinerja Dosen, 2025)
Adolescent development sooner or later will experience changes, especially in their lifestyle. Especially people's lifestyles on fast food consumption patterns (fast food). The purpose of this research is to determine teenagers' interests, opinions and activities regarding purchasing fast food in Lamongan District, Lamongan Regency. The sample used was a total of teenagers aged 16-18 years in Lamongan District, Lamongan Regency. The sampling technique uses accidental sampling until 125 respondents were obtained. This research uses quantitative descriptive research with a survey and design research approach cross sectional. This research instrument uses a questionnaire. The data analysis technique uses descriptive percentage analysis. The results of this research show that teenagers' interest tends to lead to information seeking and repeat purchases fast food. Teenagers' opinions tend to focus on the safety of long-term consumption and the impact of consumption fast food. Teenagers' activities tend to lead to purchases fast food ≥ 3 times a week and time of purchase. And purchasing decisions tend to be driven by teenagers' opinions and activities. Adolescents' opinions that are in line with their beliefs will rarely involve consuming activities fast food, while opinions that do not match beliefs will influence excessive consumption fast food.